The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1097/jgp.0b013e31818cd3be
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults' Help-Seeking Attitudes and Treatment Beliefs Concerning Mental Health Problems

Abstract: Objectives-Older adults with mental health problems are especially unlikely to seek professional mental health services. It is not clear, however, whether their help-seeking attitudes and treatment beliefs contribute to this problem. The objectives of this study were to compare older adults' attitudes and beliefs to younger adults' and to examine the influence of age on these variables after controlling for other demographic variables, prior help-seeking, and mental disorders.Methods-We analyzed cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
99
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 42 publications
(68 reference statements)
11
99
0
1
Order By: Relevance
“…Furthermore, the participants seldom reported fear of being stigmatized as a reason for not seeking help. These results are in line with recent findings, which indicate that older adults are progressively open to mental health treatment, displaying positive attitudes towards help seeking (Mackenzie, Scott, Mather, & Sareen, 2008;Mohlman, 2012;Segal, Coolidge, Mincic, & O'Riley, 2005). Nevertheless, the likelihood of seeking help for mental health problems still decreased with age.…”
Section: Page 7 Of 16supporting
confidence: 82%
“…Furthermore, the participants seldom reported fear of being stigmatized as a reason for not seeking help. These results are in line with recent findings, which indicate that older adults are progressively open to mental health treatment, displaying positive attitudes towards help seeking (Mackenzie, Scott, Mather, & Sareen, 2008;Mohlman, 2012;Segal, Coolidge, Mincic, & O'Riley, 2005). Nevertheless, the likelihood of seeking help for mental health problems still decreased with age.…”
Section: Page 7 Of 16supporting
confidence: 82%
“…A study examining service use among older and younger adults found that older adults rated the mental health treatment they received as very beneficial and this did not differ significantly from younger adults (Karlin, Duffy, & Gleaves, 2008). Similarly, studies examining older adults' attitudes towards services and beliefs about their effectiveness have found that they did not differ significantly from younger adults' (Mackenzie, Scott, Mather, & Sareen, 2008;Robb, Haley, Becker, Polivka, & Chwa, 2003).…”
mentioning
confidence: 91%
“…Les préjugés et les moyens financiers étant les deux principales barrières face à la recherche d'aide concernant des problèmes de santé mentale (Gould & al., 2012 ;Pitman & Osborn, 2011), les services d'aide téléphonique remédient à ces obstacles de par la gratuité et l'anonymat des services. Mackenzie et al (2008) (Putman, 2008).…”
Section: Les Principales Caractéristiques Des Appelants Réguliersunclassified